An analysis of euro area bond maturities and simulation of the introduction of new CACs - Frederik Eidam (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2016)
This paper studies the maturity structure of sovereign debt in the euro area and the penetration of the sovereign debt stock with a new type of collective action clauses (CACs), labeled Creditor Participation Clauses (CPCs). The first section describes the data. The simulation assumptions for the penetration of the sovereign debt stock with newly issued CPC bonds are described in section two. Section three presents the simulation results.
Keywords: 330; Öffentliche Anleihe; Fälligkeit; Eurozone